Dose-related effects of delta-9-THC on emotional responses to acute psychosocial stress - Childs, Emma; Lutz, Joseph A.; de Wit, Harriet (Drug and alcohol dependence, 2017)
•We assessed effects of delta-9-THC on responses to the Trier Social Stress Test (TSST) in healthy volunteers.•THC produced nonlinear dose effects upon emotional responses to the TSST.•7.5mg THC dampened negative emotional responses without influencing performance.•12.5mg THC slightly but significantly increased negative affect overall.•12.5mg THC impaired TSST performance and attenuated blood pressure responses. Cannabis smokers often report that they use the drug to relax or to relieve emotional stress. However, few clinical studies have shown evidence of the stress-relieving effects of cannabis or cannabinoid agonists. In this study, we sought to assess the influence of delta-9-tetrahydrocannabinol (THC), a main active ingredient of cannabis, upon emotional responses to an acute psychosocial stressor among healthy young adults. Healthy volunteers (N=42) participated in two experimental sessions, one with psychosocial stress (Trier Social Stress Test, TSST) and another with a non-stressful task, after receiving 0 (N=13), 7.5mg (N=14) or 12.5mg (N=15) oral THC. Capsules were administered under randomized, double blind conditions, 2.5h before the tasks began. We measured subjective mood and drug effects, vital signs and salivary cortisol before and at repeated times after the capsule and tasks. Subjects also appraised the tasks, before and after completion. In comparison to placebo, 7.5mg THC significantly reduced self-reported subjective distress after the TSST and attenuated post-task appraisals of the TSST as threatening and challenging. By contrast, 12.5mg THC increased negative mood overall i.e., both before and throughout the tasks, and pre-task ratings of the TSST as threatening and challenging. It also impaired TSST performance and attenuated blood pressure reactivity to the stressor. Our findings suggest that a low dose of THC produces subjective stress-relieving effects in line with those commonly reported among cannabis users, but that higher doses may non-specifically increase negative mood.